The lived experience of Chinese medical tourists receiving cancer care: A qualitative study - Tuzhen Xu; Fuqin Liu; Sandra K. Cesario; Brenda Moore (Wiley, 2023)
Abstract Aim The purpose of this study was to describe and explore the lived experience of Chinese medical tourists receiving cancer care in clinical settings in the United States. Design A qualitative phenomenological design. Methods In this study, Hermeneutic phenomenology was used to interview 11 participants on WeChat, a popular social media platform of China. Hermeneutic phenomenology methods and hermeneutic circles were used to analyse data. Results Five themes identified were: the application process involves various challenges; overcoming transportation and language barriers; feeling content with healthcare received in the United States; nearly perfect experience, except for long waiting times; and high cost of being a medical tourist. Conclusion Despite the cost and complexity of cancer treatment, Chinese medical tourists valued their experience in US clinical settings. Although, they experienced real challenges, they overcame obstacles with self‐determination and varied resources. Therefore, culturally appropriate healthcare is highly recommended. Relevance to clinical practice The findings of this study are relevant for clinical practice, particularly cancer care to medical tourists in the United States. To better support the Chinese medical tourists with cancer, various strategies and techniques, as reported in this study, could be helpful. It is highly recommended to provide healthcare providers to enable them to understand and respect the diversity norms of other cultures.